2016
DOI: 10.1094/phyto-10-15-0277-r
|View full text |Cite
|
Sign up to set email alerts
|

Pepino mosaic virusRNA-Dependent RNA Polymerase POL Domain Is a Hypersensitive Response-Like Elicitor Shared by Necrotic and Mild Isolates

Abstract: Pepino mosaic virus (PepMV) is an emerging pathogen that represents a serious threat to tomato production worldwide. PepMV-induced diseases manifest with a wide range of symptoms, including systemic necrosis. Our results showed that PepMV accumulation depends on the virus isolate, tomato cultivar, and environmental conditions, and associates with the development of necrosis. Substitution of lysine for glutamic acid at position 67 in the triple gene block 3 (TGB3) protein, previously described as a necrosis det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 66 publications
1
28
0
Order By: Relevance
“…In this context, it has been previously demonstrated that certain domains of viral proteins are essential for pathogenicity 28 , 30 . Similar necrosis-like symptoms were also observed in N. benthamiana overexpressing the TGB3 and polymerase domain of the RdRp protein of the pepino mosaic virus 31 . In the present study, we showed that 10 amino acids of the N-terminal region are essential for the development of necrotic symptoms, suggesting role in the symptom severity.…”
Section: Discussionsupporting
confidence: 70%
“…In this context, it has been previously demonstrated that certain domains of viral proteins are essential for pathogenicity 28 , 30 . Similar necrosis-like symptoms were also observed in N. benthamiana overexpressing the TGB3 and polymerase domain of the RdRp protein of the pepino mosaic virus 31 . In the present study, we showed that 10 amino acids of the N-terminal region are essential for the development of necrotic symptoms, suggesting role in the symptom severity.…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, this single nucleotide substitution might have a great impact on the biological properties of the virus. At low temperatures, about 22–23 °C, necrotic isolates of the virus replicate faster and cause strong necrosis on plants, whereas at higher temperatures (above 25 °C) replication of these virus variants is slower and in consequence necrotic symptoms are not visible [44, 52]. Here we have shown that this necrotic mutation has a neutral effect on virus fitness.…”
Section: Discussionmentioning
confidence: 75%
“…Overexpression of both TGB3 gene and the polymerase domain (POL) of the RdRp gene plays an important role in necrosis induction. The development of necrotic symptoms depends on virus accumulation level and can be modulated by tomato cultivar and environmental conditions [44]. Moreover, this single nucleotide substitution might have a great impact on the biological properties of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…PepMV symptom severity characteristics do not correlate with virus genotypes although enhanced symptom severity occurred upon mixed infections with PepMV mild and aggressive strains that belonged to different genotypes [ 27 ]. Environmental conditions, tomato cultivars and an enhanced virus accumulation are factors affecting symptom severity [ 28 ]. In addition, nonsynonymous nucleotide sequence variations have been shown to differentiate between aggressive and mild/attenuated PepMV strains [ 24 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%